On the go - Morris, Ann, 1930-; Heyman, Ken (Scott Foresman, 1993)
Discusses the ways in which people all over the world move from place to place, including walking, riding on animals, and traveling on wheels and water.
2.8
K-3.
K-3
Keywords: Transportation -- Juvenile literature; Transportation; Transportation; Picture books for children